A HS-SPME Arrow/GC-MS Method for Determination of Smoke Taint-Related Volatile Phenols in Humulus lupulus. (7th April 2022) - Williams, Stacey; Alexander, Justin
Abstract: With a record-breaking fire season across the Western US, an unknown number of food crops were exposed to significant quantities of smoke. Due to the length of the season, Humulus lupulus (hops) were exposed to smoke prior to harvest and during processing. The class of compounds from smoke with low flavor thresholds (with the potential to impact beer quality/flavor) are volatile phenolics (VPs). Guaiacol and 4-methylguaiacol (4MG) are routinely used as markers to determine the extent of smoke-taint in the wine industry. To quantify the potential flavor impact that hops exposed to smoke could have on finished beer requires a sensitive GC-MS detection method. Quantitating these compounds in smoke-exposed hops prior to use in the brewing process is needed to predict the likelihood of perceptible smoke taint in finished beer. This paper encompasses the validated analytical method to accurately quantitate unbound guaiacol and 4-methylguaiacol in smoke-exposed hops. The GC-MS method demonstrated good precision, specificity, recovery, and accuracy when measuring for the specified volatile phenols in raw hops and prepared hop teas. The method was used to demonstrate that smoke-tainted hops, when compared to control hops, show quantifiable levels of volatile phenols of interest in both raw hops and hop teas.